The Implementation of the Teaching Factory Learning Model and Its Influence on Student Work Results and Consumer Satisfaction - Bakar, Muhammad Jamil; Jalinus, Nizwardi; Milana, Milana; Sari, Delima Yanti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This article is the result of field research in three schools in Aceh Besar. This research consists of two related studies. The first focuses on answering the hypothesis about the effect of implementing a teaching factory on student work using the one-group pretest-posttest design method. Students will be given a pretest first to assess the results of their initial work. After that, they are given the teaching factory treatment and then a post-test for the results to be compared to assess whether the treatment has an effect. The second research the author wants to examine in this article is consumer satisfaction with the work. Using the survey method, the data obtained is calculated based on the satisfaction references percentage. The sample in this study consisted of 30 students to evaluate work results using the one-group pretest-posttest design method and 30 consumers to assess the level of consumer satisfaction with student work. Based on the data obtained, the researchers concluded that there was a significant influence on student work results after treatment. The average post-test result increased to a pretest value of 18.66667 with sig. 0.000, which means significant. The result value of the t count is 37.405, greater than the t table of 2.045, which means that the application of teaching factory learning is very effective in improving student work results. Then for the consumer satisfaction results, it was obtained that 30% were very satisfied with the student work, and 70% were satisfied with the student work. With nine people feeling very satisfied and 21 people feeling satisfied, the average result is that consumers are satisfied with students’ work.